Strengthening Public Financial Integrity Through Internal Control and Internal Audit Strategies - Yuspico Cornelis; Victor Cornelis (The Indonesian Accounting Review, 2026)
Fraud prevention plays an important role in improving accountable and transparent financial management in the public sector. This study aims to examine the effects of internal control systems and internal audits on fraud prevention in the Ambon City Government. A quantitative explanatory approach was used. Data were collected through questionnaires distributed to 60 employees involved in financial management within regional government organizations and were analyzed using SmartPLS. The findings indicate that internal control systems have a positive and significant effect on fraud prevention, with a path coefficient of 0.432, while internal audits also have a positive and significant effect, with a coefficient of 0.387. The R-squared value of 0.507 indicates that both variables explain 50.7% of the variance in fraud prevention. These findings suggest that fraud prevention becomes more effective when preventive and evaluative governance mechanisms are integrated. This study contributes to the public sector governance literature by positioning internal control systems and internal audits as complementary governance mechanisms that support accountability and transparency in local government financial management.